PENGARUH TANAMAN PICUNG (Pangium edule) DAN SERAI WANGI (Cymbopogon nardus) TERHADAP MORTALITAS PENGGEREK BUAH KOPI (Hypothenemus hampei) - Fadilah, Fitriyatul; Setyo Andi Nugroho; Nuraisyah, Anni; Wardati, Irma; Novenda, Ika Lia (JURNAL BIOSENSE, 2024)
Coffee (Coffea sp.) is one of the main commodities in Indonesia. According to the Plantation Statistics data for 2019-2021, coffee production decreased by approximately 3,540 tons in 2019. One factor contributing to the decline in coffee quality is the attack of the coffee berry borer Hypothenemus hampei Ferr. The picung plant contains 1000-2000 ppm cyanide acid, flavonoids, alkaloids, and saponins, which are lethal and can poison pests, while the citronella plant contains 37 types of compounds, with the highest content being citronella (35.97%). The study used a Factorial Completely Randomized Design (RALF) and was further tested using the BNJ method. The results showed that the botanical insecticides from picung and citronella extracts were effective against coffee berry borer pests, with the fastest mortality reaching up to 80% death in the P3S3 treatment (144 hours), with the fastest LT50 value (91 hours), and the smallest feeding rate value of 0.08 grams.